The dynamics of catch-up and skill and technology upgrading in China - Xi Chen; Michael Funke (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This paper accounts for China.s economic growth since 1980 in a unified endogenous growth model in which a sequencing of physical capital accumulation, human capital ac-cumulation and innovation drives the rise in China.s aggregate income. The first stage is characterized by physical capital accumulation. The second stage includes both physical and human capital accumulation, and in the final stage innovation is added to the mix. Model calibrations indicate that the growth model can generate a trajectory that accords well with the different stages of development in China.
URN:NBN:fi:bof-201408071999
Keywords: D90; O31; O33; O41; 330; China; economic growth; transitional dynamics